Catheter-directed treatment for acute pulmonary embolism: Systematic review and single-arm meta-analyses. (15th December 2016) - Bajaj, Navkaranbir S.; Kalra, Rajat; Arora, Pankaj; Ather, Sameer; Guichard, Jason L.; Lancaster, W. Jake; Patel, Nirav; Raman, Fabio; Arora, Garima; Al Solaiman, Firas; Clark, D. Trey; Dell'Italia, Louis J.; et al.
Abstract: Background: We sought to estimate the efficacy and safety outcomes of catheter-directed treatment (CDT) for patients with acute pulmonary embolism (PE). Methods: We searched SCOPUS for studies reporting outcomes after CDT for acute PE. Studies were categorized in three groups for analyses due to heterogeneity in the classification of acute PE: 1) patients with PE causing right ventricular dysfunction and haemodynamic instability: unstable haemodynamic status, 2) patients with PE causing right ventricular dysfunction where study outcomes were not stratified by haemodynamic status: stable and unstable haemodynamic status, and 3) patients with PE causing right ventricular dysfunction who remained haemodynamically stable: stable haemodynamic status. Efficacy and safety outcomes were estimated and presented as point estimates with 95% confidence intervals. Results: In 35 studies with 1253 patients, 1277 CDTs were performed. The in-hospital mortality rates for the unstable haemodynamic status, stable and unstable haemodynamic status, and stable haemodynamic status groups were 18.1% (7.3–38.2%), 7.1% (5.0–10.1%), and 2.6% (0.8–7.3%), respectively. The major bleeding rates across the groups were estimated to be 4.5, 8.5 and 3.9 per 100 CDTs, respectively. Minor bleeding occurred in 6.2, 11.9 and 9.1 per 100 CDTs, respectively. After CDT, all groups had improvements in mean pulmonary artery pressure and right ventricular function. Conclusions: We provide descriptive measures of efficacy and safety for patients who underwent CDT for acute PE.